2019
DOI: 10.1002/jcp.28994
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated N6‐methyladenosine methylation writer METTL3 contributes to the proliferation and migration of gastric cancer

Abstract: Accumulating evidence implies that N6-methyladenosine (m6A) methylation participated in the tumorigenesis of gastric cancer (GC). Here we synthetically analyzing the prognostic value and expression profile of seven m6A methylation-relevant genes through silico analysis of sequencing data downloaded from The Cancer Genome Atlas, Kaplan-Meier plotter, and Gene Expression Omnibus database. We explored the methyltransferase-like 3 (METTL3) expression in GC cell line and tumor tissues by reverse transcription quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 62 publications
4
81
0
Order By: Relevance
“…m6A RNA modification is a hotspot in the field of regulation in recent years, involving multiple cellular processes such as mRNA maturation, protein translation and molecular structure transformation . There is growing evidence that m6A dysregulation has a profound impact on the pathogenesis of many diseases, including GC . We examined the expression of WTAP in GC samples and found that WTAP expression in tumour tissues was higher than that in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…m6A RNA modification is a hotspot in the field of regulation in recent years, involving multiple cellular processes such as mRNA maturation, protein translation and molecular structure transformation . There is growing evidence that m6A dysregulation has a profound impact on the pathogenesis of many diseases, including GC . We examined the expression of WTAP in GC samples and found that WTAP expression in tumour tissues was higher than that in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, METTL3 can promote pri-miRNA processing by interacting with DGCR8 (2,20,54). Dysregulation of METTL3 in various cancers can also influence cancer cell EMT (23,49,50), apoptosis (36,47), and stem cell self-renewal (38,39), which have been identified to be important in cancer progression. In addition, METTL3-mediated m 6 A modification can directly regulate the transcription and translation of oncogenes and tumor suppressors coupled to the most of the important pathways involved in cancer cell progression, such as the PI3K/AKT (36,44,47,57,60,62), wnt/βcatenin (46), and P38/ERK (26) pathways.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…METTL3 and m 6 A were upregulated in human osteosarcoma (46), gastric cancer (23,47,48), melanoma (49), ovarian carcinoma (50), and hepatocellular carcinoma (51). Its expression level gradually increased with the increasing tumor stage and grade.…”
Section: Mettl3 In Other Cancersmentioning
confidence: 95%
See 1 more Smart Citation
“…The METTL3 RNA methyltransferase is a "writer" protein responsible for m 6 A modification and is involved in mRNA biogenesis, decay, and translation. METTL3 may play a carcinogenic role in lung cancer [39], bladder cancer [23,40], gastric cancer [41], osteosarcoma [42], cutaneous squamous cell carcinoma [43], and acute myeloid leukemia (AML) [44]. Li et al [45] reported that METTL3 promoted colorectal cancer progression through an m 6 A-IGF2BP2dependent mechanism, while Deng et al [46] reported that METTL3 inhibited the proliferation and migration of colorectal cancer cells through the p38/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%